Prioritizing Urban Radiation Monitoring Using Background Radiation Levels and Population Density: A Bandung Case Study - Saumi Zikriani Ramdhani; Devi Nurhanivah; Ayesha Bilqis; Abiel Bariq (Indonesian Journal of Science and Education, 2025)
This study investigated background radiation in Bandung City by integrating field measurements with demographic data to establish monitoring priorities. Data were collected from 60 sampling points across ten densely populated districts, covering six land-use types: open areas, residential neighborhoods, offices, healthcare facilities, industrial or waste sites, and waterways. Radiation levels were measured using a handheld Geiger–Müller counter in counts per minute (CPM) and were analyzed using medians, quartiles, interquartile ranges (IQR), and 95th percentiles (P95). Differences among districts were tested with the Kruskal–Wallis method. The citywide baseline was determined at 21 CPM, with district medians ranging from 16.5 to 23.5 CPM. Although several districts showed slightly higher or lower values, statistical results (p ≈ 0.111) indicated that the variation was not significant. Wider IQR values in some districts reflected localized heterogeneity, while Districts I and E recorded the highest P95 values. To refine monitoring priorities, a Population-Weighted Index (PWI) was applied by combining radiation levels with population data. Districts E, A, and C were identified as priority areas because of their relatively higher CPM values, larger populations, or both. Overall, the findings suggested that while background radiation levels in Bandung remained within natural ranges, incorporating demographic factors into radiation assessments provided a more effective approach for prioritizing urban monitoring, managing potential risks, and supporting public health planning.